Endo-Approximately 2-Absorbing Submodule and Module - Kadhim , Safa Hussam; Shyaa, Farhan Dakhil (Iraqi Journal of Science, 2024)
In this paper we introduce the concept of Endo-approximately 2-absorbing sub- module (shortly EATA) as a generalization of Endo 2-absorbing sub-module , where A proper sub-module N of an R-module Μ is called an EATA sub-module  if for all f, g ∈ EndM, x∈M, f∘g(x) ∈ N implies the f^2 (x) ∈N or g^2 (x) ∈N or f^2∘g^2  (M) ⊆N. Many basic properties, characterization and examples of this concept are given.